Bauer, Jean-Martin. The New Breadline: Hunger and Hope in the Twenty-First Century - Bellemare, Marc F. (Journal of Economic Literature, 2025)
Marc F. Bellemare of University of Minnesota reviews “The New Breadline: Hunger and Hope in the Twenty-First Century” by Jean-Martin Bauer. The Econlit abstract of this book begins: “Examines the societal causes of and solutions to hunger, highlighting the systems of racism, classism, and sexism that prevail in hunger-prone countries.”